Perlindungan hukum terhadap perjanjian endorsement (jasa promosi) yang dilakukan oleh selebgram pada media sosial instagram ditinjau dari perspektif kitab undang undang hukum perdata - Nisa, Rauzatul; Sulaiman, Sulaiman; Jafar, Sofyan (Fakultas Hukum Universitas Malikussaleh, 2024)
This research aims to find out what form of legal protection there is for endorsement agreements (promotional services) made by celebgrams on Instagram social media from a Civil Code perspective, as well as to find out what form endorsement agreements (promotional services) made by celebgrams on Instagram social media look from. Civil Code perspective. This research uses a normative juridical method which places the law as a norm. The result of this research is that the form of legal protection for endorsement agreements made by celebs on Instagram social media can refer to Article 1320 of the Civil Code, that the agreement is valid based on the conditions for the validity of the agreement. However, it can be detrimental to the online shop because of the imbalance in the position of the parties caused by the agreement mechanism which is only through agreeing to the terms and conditions made unilaterally by the celebgram, without any negotiation.